Effect of misalignment on shear response of plain woven fabric in picture frame test: experiments and finite element modelling. Issue 10 (2nd October 2016) - Lin, Guochang; Yuan, Xuebo; Luo, Xilin; He, Ge; Tan, Huifeng
Abstract : Picture frame test on woven fabrics is not completely controlled and misalignment is one of the tremendous factors. The aim of this study was to investigate the effect of misalignment on the shear response of plain woven fabric in picture frame test. Misaligned and aligned specimens of plain woven fabric were tested, and digital image correlation (DIC) technique was applied to map the strain displacement fields. Unit cell models of misaligned and aligned specimens were built to simulate the mechanical behaviours during the shear test. Simulated and experimental results showed reasonable agreement. Strain fields mapped by DIC and averaged strains obtained by FEM simulation both demonstrate that tension or compression is introduced by misalignment. Deformation mechanism of misaligned fabric is discussed.